Long-Term Exposure to Ceftriaxone Sodium Induces Alteration of Gut Microbiota Accompanied by Abnormal Behaviors in Mice - Zhao, Zhongyi; Wang, Baoning; Mu, Liyuan; Wang, Hongren; Luo, Jingjing; Yang, Yuan; Yang, Hui; Li, Mingyuan; Zhou, Linlin; Tao, Chuanmin (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Growing evidence points out that disturbance of gut microbiota may disturb gut–brain communication. However, it is not clear to what extent alteration of microbiota composition can modulate the brain function, thus affecting host behaviors. Here we investigated the effects of gut microbiota depletion on emotional behaviors. Methods: Mice in experimental group were orally administered with ceftriaxone sodium solution (250mg/ml, 0.2ml/d) for eleven weeks. The open field test and tail suspension test were employed for neurobehavioral assessment of the mice. Fecal samples were collected for 16s rDNA sequencing. Serum levels of cytokines and corticosterone were quantified using enzyme linked immunosorbent assays. Immunohistochemistry method was used for detection of brain derived neurotrophic factor (BDNF) and c-Fos protein. Results: The gut microbiota for antibiotic-treated mice showed lower richness and diversity than normal controls. This effect was accompanied by increased anxiety-like, depression-like and aggressive behaviors. And then we found these changes might be associated with a dysregulation of immune system, abnormal activity of hypothalamic-pituitary-adrenal axis and alteration of neurochemistry. Conclusions: The findings demonstrate the indispensable role of microbiota in the gut–brain communication and suggest the absence of conventional gut microbiota could affect the nervous system, influencing brain function.